DISPOSAL LIQUEFACTION POTENTIAL ANALYSIS BASED ON WASTE DUMP STABILITY RATING HAZARD CLASSIFICATION SYSTEM (WSRHC) METHOD AT DISPOSAL TAMBANG AIR LAYA, SOUTH SUMATRA - Aprilian, Yoga; Zakaria, Zufialdi; Khoirullah, Nur; Ersyari, Jodistriawan; Chen, Reynara Davin (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
South Tambang Air Laya Disposal is an inpit disposal located in an active tectonic area adjacent to the active Sumatran Fault Zone. Area's support this with a peak acceleration value of 0.2 – 0.25. One of the causes of liquefaction is the presence of shocks or earthquakes. For this reason, it is necessary to analyze the liquefaction potential to determine the liquefaction potential, especially in the disposal material and the disposal foundation of the research area. The method used in this research is the Waste Dump Stability Rating Hazard Classification System; this method is used to assess the liquefaction potential at the disposal, divided into two parts, namely the liquefaction potential at the foundation and the liquefaction potential at the disposal material. The data used in this research include secondary data from seismic factor data, South Sumatra earthquake zone data, South Sumatra liquefaction zone data, and laboratory test results of disposal foundations. In addition, data on the results of physical and mechanical properties of the disposal material were used in the form of grain size gradation data and data from plasticity test results. All the data used shows that the liquefaction potential of the disposal foundation is included in a negligible category with a rating value of 0. Meanwhile, the potential for liquefaction of disposal material is included in the low category with a rating value of -2.5, which must still be considered to avoid unexpected things that can occur.